Hyperechoic pancreas on ultrasonography: an analysis of its severity and clinical implications - Oh, Hyunji; Park, Hyun Jeong; Oh, Jiyun; Lee, Eun Sun; Park, Sung Bin; Cha, Min Jae; Ahn, Soohyun (Ultrasonography, 2022)
Purpose: This study investigated risk factors for hyperechoic pancreas (HP) on ultrasonography (US) according to HP severity. Methods: Between December 2008 and February 2014, 1,459 subjects who underwent abdominal US as part of health examinations were retrospectively included. Two radiologists assessed and categorized the severity of HP as normal, mild, moderate, and severe. Subjects were allocated to two groups as follows: fatty pancreas 1 (FP1; mild to severe HP) and fatty pancreas 2 (FP2; moderate to severe HP). Clinico-metabolic parameters such as the body mass index and blood test profile of subjects with normoglycemia and prediabetes/diabetes were compared (normal vs. FP1; normal or mild HP vs. FP2). Logistic regression analysis was used to evaluate the associations between HP, nonalcoholic fatty liver disease (NAFLD), and diabetes/prediabetes with adjustment for clinico-metabolic parameters. Results: Of the 1,459 subjects, 71.2% and 40.4% showed HP and NAFLD on US, respectively. Normoglycemia and prediabetes/diabetes were present in 74.3% and 25.7% of subjects, respectively. Univariable analysis revealed that all the clinico-metabolic parameters were significantly associated with HP (all P<0.05). In the adjusted multivariable analysis, prediabetes/ diabetes, NAFLD, age, and body mass index were significantly associated with HP with the FP1 and FP2 criteria. The independent factor with the strongest association with HP was NAFLD using the FP1 criterion (odds ratio [OR], 7.93; P<0.001) and prediabetes/diabetes using the FP2 criterion (OR, 6.96; P<0.001). Conclusion: NAFLD and prediabetes/diabetes were associated with US-diagnosed HP. Moderate to severe HP was a better predictor of prediabetes/diabetes, suggesting that evaluating HP severity may be useful in clinical practice.
Keywords: Diabetes; Fatty pancreas; Hyperechoic pancreas; Nonalcoholic fatty liver disease; Ultrasonography